2010
DOI: 10.1002/chem.200902382
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Metal–Organic Framework Material, Iron Terephthalate, by Ultrasound, Microwave, and Conventional Electric Heating: A Kinetic Study

Abstract: A metal-organic framework material named MIL-53(Fe), iron terephthalate, has been synthesized sovothermally at a relatively low temperature by not only conventional electric (CE) heating, but also by irradiation under ultrasound (US) and microwave (MW) conditions to gain an understanding of the accelerated syntheses induced by US and MW. The kinetics for nucleation and crystal growth were analyzed by measuring the crystallinity of MIL-53(Fe) under various conditions. The nucleation and crystal growth rates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(144 citation statements)
references
References 116 publications
12
127
0
5
Order By: Relevance
“…1a, MIL-53(Fe) exhibits a sphere-like shape with an average size of about 600 nm. Also, it can be observed that these MIL-53(Fe) particles have good uniformity, which is consistent with previous reports [33]. The XRD pattern of the prepared MIL-53(Fe) in Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1a, MIL-53(Fe) exhibits a sphere-like shape with an average size of about 600 nm. Also, it can be observed that these MIL-53(Fe) particles have good uniformity, which is consistent with previous reports [33]. The XRD pattern of the prepared MIL-53(Fe) in Fig.…”
Section: Resultssupporting
confidence: 91%
“…The XRD pattern of the prepared MIL-53(Fe) in Fig. 1b was consistent with previous reports [32,33]. It is noted that the XRD pattern of MIL-53(Fe) after CL reaction was almost the same as that of the original MIL-53(Fe) (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Potentially, MOF materials can be applied in numerous industrial applications including gas separation, adsorption and storage processes [15,16], heterogeneous catalysis [7], pharmaceutical manufacturing processes and drug delivery [10]. Carbon dioxide (CO 2 ) is one of the main green house gases, which is known for its harmful effect on global warming and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…However, accelerated MW-syntheses of Cu 2 O [16], molecular sieves like AlPO-11 and SAPO-11 [17] and metal-organic frameworks (MOFs) such as ironbenzenedicarboxylate [18] and copper-benzenetricarboxylate [19] are mainly due to a very large increase in pre-exponential factors (even with increased E a ). Very recently, Ahnfeldt et al [20] have shown the accelerated synthesis of a MOF (CAU-1-(OH) 2 ) with MWs is due to an increase of pre-exponential factor.…”
Section: Resultsmentioning
confidence: 99%